RANCANGAN DASAR SISTEM KENDALI UMPAN MAJU PADA SISTEM KEMUDI EMPAT RODA BERDASARKAN MODEL KENDARAAN PENUH - Sampurno, B; Tjokronegoro, H. A; I. M, Farida; Arismunandar, W (Mesin, 2001)
This paper discribes a basic design of feed forward controller on a four wheel steering (4WS) vehicle. The controller directs all wheels to get an optimal maneuver. Controlling the wheels is done by controlling each sideslip angles (Î²i). The sideslip angles are computed by estimating slip angles (Î±i). Estimation of slips angles are done by sideslip angles based on full car model. The mathematical model is computed based on all forces that work on each wheels.